Curriculum reform: Why? What? How? and how will we know it works? - Shmuel Reis (BMC, 2018)
Abstract In a recent IJHPR article, Dankner et al. describe a reform in one longitudinal strand within Basic Medical Education i.e." public health and preventive medicine curriculum" using a Competency Based Medical Education approach. This reform raises several concerns: What should prompt a medical school to change a curriculum? How should such change be conducted? What kinds of paradigms may inform such a change? What constitutes a success in a curricular reform? And, how can curricular reform be evaluated within a reasonable time framework? This commentary addresses these concerns and concludes that curricular reform should follow as much as possible the current wisdom of educational innovation and change strategy, follow a clear vision, mission, and selected educational paradigm, and pay attention to stakeholders, context, culture and politics. The design should allow for the emergence of unintended consequences. Implementation needs careful planning and monitoring and the evaluation should be multi-faceted. Finally, since all Israeli medical schools are now using the Competency Based Medical Education approach and aligning their curricula and testing accordingly, a fascinating collaborative opportunity exists to professionalize this process and hopefully make a positive impact.